2010
DOI: 10.1113/jphysiol.2010.191510
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue preconditioning increases fatigue resistance in mouse flexor digitorum brevis muscles with non‐functioning KATP channels

Abstract: The objective of this study was to determine how an initial fatigue bout (FAT1 at 37 ] i /force were slower during FAT2 elicited 60 min after FAT1. Under control conditions, the effects were small with very few significant differences. In the presence of glibenclamide, on the other hand, the differences between FAT1 and FAT2 were very large. Unexpectedly, the differences in unstimulated and tetanic [Ca 2+ ] i /force between control and glibenclamide conditions observed during FAT1 were no longer observed durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…, ; Boudreault et al. ), including large membrane depolarization, large increases in unstimulated [Ca 2+ ]i and force resulting in apparent faster fatigue rate and lower capacity to recover following fatigue. Here, we again showed that compared to control fibers the absence of KATP channel activity resulted in significantly greater proportions of fibers with (1) decreases in tetanic [Ca 2+ ]i exceeding 0.5 μmol/L, (2) fade, and (3) complete failure to release Ca 2+ upon stimulation (the latter observed with glibenclamide‐exposed fibers).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…, ; Boudreault et al. ), including large membrane depolarization, large increases in unstimulated [Ca 2+ ]i and force resulting in apparent faster fatigue rate and lower capacity to recover following fatigue. Here, we again showed that compared to control fibers the absence of KATP channel activity resulted in significantly greater proportions of fibers with (1) decreases in tetanic [Ca 2+ ]i exceeding 0.5 μmol/L, (2) fade, and (3) complete failure to release Ca 2+ upon stimulation (the latter observed with glibenclamide‐exposed fibers).…”
Section: Discussionmentioning
confidence: 99%
“…[Ca 2+ ]i was then calculated from the ratio as previously described (Boudreault et al. ) using the following equation: false[normalCa2+false]i=Kd(RRmin)(RmaxR)β where,…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations